2023
DOI: 10.21037/qims-22-583
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-related differences in cortical morphology and their relationships with cognitive performance in healthy middle-aged and older adults

Abstract: Background The impacts of age and sex on brain structures related to cognitive function may be important for understanding the role of aging in Alzheimer disease for both sexes. We intended to investigate the age and sex differences of cortical morphology in middle-aged and older adults and their relationships with the decline of cognitive function. Methods In this cross-sectional study, we examined the cortical morphology in 204 healthy middle-aged and older adult part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…With respect to the presence and direction of the observed sex effect (women > men), the current findings confirm some prior studies, which reported an increased gyrification in females compared to males in parietal regions (Gautam et al, 2015), frontal and parietal regions (Cui et al, 2023;Luders et al, 2004), or frontal, parietal, temporal and occipital regions (Luders et al, 2006). With respect to the location of the sex effect, there is a striking correspondence with the outcomes of another recent study (Cui et al, 2023) based on 204 healthy adults (127 women / 77 men): More specifically, when investigating the gyrification index, Cui et al ( 2023) reported very similar regions where women had increased measures compared to men (see fig. 4 in Cui et al, 2023).…”
Section: Correspondence With Prior Findingssupporting
confidence: 91%
“…With respect to the presence and direction of the observed sex effect (women > men), the current findings confirm some prior studies, which reported an increased gyrification in females compared to males in parietal regions (Gautam et al, 2015), frontal and parietal regions (Cui et al, 2023;Luders et al, 2004), or frontal, parietal, temporal and occipital regions (Luders et al, 2006). With respect to the location of the sex effect, there is a striking correspondence with the outcomes of another recent study (Cui et al, 2023) based on 204 healthy adults (127 women / 77 men): More specifically, when investigating the gyrification index, Cui et al ( 2023) reported very similar regions where women had increased measures compared to men (see fig. 4 in Cui et al, 2023).…”
Section: Correspondence With Prior Findingssupporting
confidence: 91%
“…Family caregivers of older people with memory problems report that the elders put themselves in danger involving situations such as lighting the gas stove and forgetting to turn it off and handling saucepans on the hotplate. Symptoms of cognitive decline can include problems remembering names, word-finding difficulties when trying to describe something, and mislaying objects 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Aging is accompanied by decline in processing speed, attention span, episodic recall ability and execution of different tasks [3][4][5] . Memory complaints in older individuals are more prevalent among women 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The PFC is a critical region for age-specific extinction (Ganella et al, 2017b;Kim et al, 2017;Zbukvic et al, 2017;Zbukvic and Kim, 2018;Perry et al, 2021). In humans, the PFC is one of the first to atrophy in aging, which is consistently related to reduced cognitive flexibility (Armstrong et al, 2019;Cui et al, 2023). Extinction could be considered a test of cognitive flexibility because it involves the flexible retrieval of the fear memory or the extinction memory depending on the appropriate circumstance (Kaczorowski et al, 2012;Short et al, 2022).…”
Section: Aging Sex DI Erences In Extinction Of Conditioned Fearmentioning
confidence: 99%